Updating the technique of caesarean section in the Maternity Institute "Alberto Peralta Ramos". II. Uterine rupture between 1950-1966 - Nolting, David (2015)
The authors present a statistical analysis of the maternal death at the Institute of Maternity "Alberto Peralta Ramos" in Buenos Aires. In 38 years of activity and with a total number of patients of 230,432, 2.25 per thousand of 517 women died; they divide this group in three subgroups: 1) 44 patients that suffered diseases due to pregnancy 2) 200 patients with diseases complicating pregnancy and 3) 265 women dead as a consequence of the obstetrical treatment. The authors observe a diminished number of deaths in pregnant women in the last years with an actual figure of 1.0 per thousand. The present in detail their experience with 20 cases of rupture of the uterus registered between 4723 deliveries; at the same hospital; all these cases were in multiparous women and 76% of them occurred in patients with previous cesarean operation; the over all  maternal mortality was 16% the fetal mortality was 75%.